The role of hospital pharmacists in supporting the appropriate and safe use of CGT/ATMPs: a scoping review of current insights - Junnan Shi; Xianwen Chen; Hao Hu; Carolina Oi Lam Ung (BMC Health Services Research)
Abstract Background The role of hospital pharmacists in managing cell and gene therapy (CGT) and advanced therapy medicinal products (ATMPs) is gradually being recognized but the evidence about impact of their role has not been systematically reported. Objective This study was aimed to summarize the professional services provided by hospital pharmacists on managing CGT/ATMPs and the evidence about the effects on patient care, as well as to identify the perceptions about pharmacists assuming a role that supports the appropriate and safe use of CGT/ATMPs. Methods Literature from 4 electronic databases (PubMed, ScienceDirect, Web of Science, Scopus) were searched following PRISMA checklist to yield publications on the interventions provided by hospital pharmacists in the management of CGT/ATMPs dated since 1 January 2013 till 30 April 2023. Results Thirty-four publications were included in this review. Eight studies involving hospital pharmacists participating in interventions for 1,012 hematopoietic stem cell transplant (HSCT) patients from 8 hospitals in 5 countries were identified. Common pharmacist-led interventions centered on medicine administration, prescribing, and monitoring of medicines use, resulting in significant improvement in patient adherence, satisfaction and knowledge. Of 26 studies, the perspectives assuming their roles in CGT/ATMPs management were categorized when patients receiving ATMPs (n = 2), HSCT and cellular-based therapy (n = 12), gene therapy (n = 6), and the chimeric antigen receptor (CAR) T-cell therapy (n = 6), mainly covering procurement, influences on prescribing, preparation and delivery, administration, monitoring of medicines use, human resources, training and development. The anticipated impact was primarily intended to promote pharmacy practice, multidisciplinary collaboration and improve patient clinical outcomes. Conclusion Leveraging the role of hospital pharmacists in multidisciplinary healthcare teams to develop a coordinated approach that supports pharmacy practice will better meet the management of CGT/ATMPs. For hospital pharmacists to step up their role in the multidisciplinary healthcare team, advancing their skillset in terms of clinical practice standards and medication management is essential.